The evaluation of pelvic floor muscle strength in women with pelvic floor dysfunction: A reliability and correlation study - Navarro Brazález, Beatriz; Torres Lacomba, María; de la Villa, Pedro; Sánchez Sánchez, Beatriz; Prieto Gómez, Virginia; Asúnsolo del Barco, Ángel; McLean, Linda (Neurourology and urodynamics, 2018)
Aims The purposes of this study were: (i) to evaluate the reliability of vaginal palpation, vaginal manometry, vaginal dynamometry; and surface (transperineal) electromyography (sEMG), when evaluating pelvic floor muscle (PFM) strength and/or activation; and (ii) to determine the associations among PFM strength measured using these assessments. Methods One hundred and fifty women with pelvic floor disorders participated on one occasion, and 20 women returned for the same investigations by two different raters on 3 different days. At each session, PFM strength was assessed using palpation (both the modified Oxford Grading Scale and the Levator ani testing), manometry, and dynamometry; and PFM activation was assessed using sEMG. Results The interrater reliability of manometry, dynamometry, and sEMG (both root‐mean‐square [RMS] and integral average) was high (Lin's Concordance Correlation Coefficient [CCC] = 0.95, 0.93, 0.91, 0.86, respectively), whereas the interrater reliability of both palpation grading scales was low (Cohen's Kappa [k] = 0.27‐0.38). The intrarater reliability of manometry (CCC = 0.96), and dynamometry (CCC = 0.96) were high, whereas intrarater reliability of both palpation scales (k = 0.78 for both), and of sEMG (CCC = 0.79 vs 0.80 for RMS vs integral average) was moderate. The Bland‐Altman plot showed good inter and intrarater agreement, with little random variability for all instruments. The correlations among palpation, manometry, and dynamometry were moderate (coefficient of determination [r2] ranged from 0.52 to 0.75), however, transperineal sEMG amplitude was only weakly correlated with all measures of strength (r2 = 0.23‐0.30). Conclusions Manometry and dynamometry are more reliable tools than vaginal palpation for the assessment of PFM strength in women with pelvic floor disorders, especially when different raters are involved. The different PFM strength measures used clinically are moderately correlated; whereas, PFM activation recorded using transperineal sEMG is only weakly correlated with PFM strength. Results from perineal sEMG should not be interpreted in the context of reporting PFM strength.